On Dubins paths to intercept a moving target. (March 2015) - Meyer, Yizhaq; Isaiah, Pantelis; Shima, Tal
Abstract: We examine the problem of interception by a Dubins vehicle of a target that moves at constant speed along an a priori known planar trajectory. We establish sufficient conditions under which the shortest interception paths coincide with the shortest Dubins paths from the initial configuration of the pursuer to the point of interception, and show by means of examples that this is not always the case if the conditions are violated. Motivated by the problem of simultaneous interception of a target by a team of pursuers, we also analyze the problem of interception at a predefined time by a single pursuer. We present three path elongation algorithms, along with conditions that guarantee continuous elongation, and provide a sufficient condition for simultaneous interception. The analysis culminates in a centralized coordination scheme for simultaneous interception.